2003
DOI: 10.1037/0022-006x.71.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Parent training of toddlers in day care in low-income urban communities.

Abstract: The authors tested a 12-week parent training program with parents (n = 208) and teachers (n = 77) of 2-3-year-olds in day care centers serving low-income families of color in Chicago. Eleven centers were randomly assigned to 1 of 4 conditions: (a) parent and teacher training (PT + TT), (b) parent training (PT), (c) teacher training (TT), and (d) waiting list control (C). After controlling for parent stress, PT and PT + TT parents reported higher self-efficacy and less coercive discipline and were observed to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
236
1
19

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(260 citation statements)
references
References 53 publications
4
236
1
19
Order By: Relevance
“…We included 48 studies that were identified by screening the full-text article against inclusion criteria (Bradley et al, 2003;Chronis, Gamble, Roberts, & Pelham, 2006;DeGarmo, Patterson, & Forgatch , 2004;Fanning, 2007;Fantuzzo Stevenson, Abdul Kabir, & Perry, 2007;Farrar, 2005;Feliciana, 2005;Gallart & Matthey, 2005;Gardner, Burton, & Klies, 2006;Gross et al, 2003;Gross et al, 2009;Gutierrez, 2007;Hanisch et al, 2010;Hiscock et al, 2008;Hutchings et al, 2007;Joachim, Sanders, & Turner, 2010;Larsson et al, 2009;Lipman & Boyle, 2005;Martin & Sanders, 2003;Matsumoto et al, 2007;Matsumoto et al, 2010;Morawska & Sanders, 2009;Niccols, 2009;Treacy, Tripp, & Baird, 2005;Turner, Richards, & Sanders, 2007;van den Hoofdakker et al, 2007;Wang, 2005;Wolfe & Hirsch, 2003). Two review authors (NS and NH) independently examined studies included in the previous review against the current review's more rigorous inclusion criteria and determined only 20 of the 26 articles met the current study's inclusion criteria.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 48 studies that were identified by screening the full-text article against inclusion criteria (Bradley et al, 2003;Chronis, Gamble, Roberts, & Pelham, 2006;DeGarmo, Patterson, & Forgatch , 2004;Fanning, 2007;Fantuzzo Stevenson, Abdul Kabir, & Perry, 2007;Farrar, 2005;Feliciana, 2005;Gallart & Matthey, 2005;Gardner, Burton, & Klies, 2006;Gross et al, 2003;Gross et al, 2009;Gutierrez, 2007;Hanisch et al, 2010;Hiscock et al, 2008;Hutchings et al, 2007;Joachim, Sanders, & Turner, 2010;Larsson et al, 2009;Lipman & Boyle, 2005;Martin & Sanders, 2003;Matsumoto et al, 2007;Matsumoto et al, 2010;Morawska & Sanders, 2009;Niccols, 2009;Treacy, Tripp, & Baird, 2005;Turner, Richards, & Sanders, 2007;van den Hoofdakker et al, 2007;Wang, 2005;Wolfe & Hirsch, 2003). Two review authors (NS and NH) independently examined studies included in the previous review against the current review's more rigorous inclusion criteria and determined only 20 of the 26 articles met the current study's inclusion criteria.…”
Section: Included Studiesmentioning
confidence: 99%
“…Therefore, considerable potential exists for interventions aimed at promoting the psychosocial wellbeing of parents to reduce the disruption to the child's emotional, educational, and social adjustment and thereby to promote the mental health of future children. Several studies have shown parenting programs can improve maternal mental health and well-being, including anxiety (Matsumoto, Sofronoff, & Sanders, 2010;Morawska & Sanders, 2009) and depression (Hanisch et al, 2012;Pisterman et al, 1992a), as well as other aspects of parental psychosocial functioning such as marital relations and parenting stress (Gross et al, 2003;Larsson et al, 2009;Todres & Bunston, 1993). However, the primary aim of such programs is to promote change in parenting practices and child functioning (Drezke et al, 2005).…”
mentioning
confidence: 99%
“…Effects were not significantly better when both parents and teachers received training. 58 The Family Check-Up is a brief intervention specifically designed for mothers of toddlers. It was evaluated with mothers of boys aged 17 to 29 months presenting at least 2 of the following risk factors: low SES, family problems (that is, maternal depression or substance use), and child conduct problem symptoms.…”
Section: Preventive Experiments For Dbdsmentioning
confidence: 99%
“…A series of randomized controlled trials conducted by the program developer (Reid, Webster-Stratton, & Baydar, 2004;WebsterStratton, 1984WebsterStratton, , 1998aWebster-Stratton & Hammond, 1997;Webster-Stratton, Kolpacoff, & Hollinsworth, 1988) and others (Brotman et al, 2005;Gross et al, 2003;Scott, Spender, Doolan, Jacobs, & Aspland, 2001;Spaccarelli, Cotler, & Penman, 1992;Taylor, Schmidt, Pepler, & Hodgins, 1998) have demonstrated that the program is effective at reducing behavior problems in children, improving parenting practices and reducing parent depression.…”
Section: Incredible Years Group Parenting Programmentioning
confidence: 99%